SPATIAL PATTERNS OF ACCESS TO RETAIL FOOD OUTLETS IN MEXICO CITY - González-Alejo, Ana Laura (2019)
This paper presents a spatial and quantitative approach to identify patterns of access to food retail and its association with urban marginalization in Mexico City. The spatial distribution of food establishments was identified using the moving windows method, in a scale of analysis of 100 m2, to delimitate areas with differentiated access to healthy and unhealthy outlets. This method revealed the spatial patterns of access to retail food outlets that are manifested with large areas of downtown, north, and east of the city exposed to an unhealthy retail food environment, while the peripheral areas of the south and southeast are under the influence of food deserts. It was revealed that 21.9% of the urban territory of the city is a healthy food environment and is distributed in the south and west of the city. It was also found that the population with the highest levels of marginalization and with medium levels are those who are exposed to unhealthy retail food environments. Chi-square test and a bivariate regression were used to determine associations between marginalization levels of the population, types of retail food environments, schooling and population density. The results indicate an association between high levels of marginalization and limited or limited access to healthy food environments, as well as a negative relationship between low levels of schooling and the density of unhealthy foods in the territory. Keywords: Food access; retail food environment; food spatial disparities.